Pluto and Charon ice worlds on the ragged edge of the solar system - Stern, Alan; Mitton, Jacqueline 1948- (Wiley, 1998)
"An interwoven tale of exotic Pluto, its unusual satellite companion Charon, and the dynamic, high-technology world of twentieth-century astronomy."--Jacket.
Literaturverz. S. 209 - 210
Keywords: Geschichte; Forschung; Charon (Satellite); Pluto (Dwarf planet); Charon -- Plutomond; Pluto -- Zwergplanet